CORPORATE SUSTAINABILITY REPORT SEBAGAI INDIKATOR PENGAMBILAN KEPUTUSAN INVESTASI - Satia Nur Maharani (University of Merdeka Malang, 2011)
One indicator of investment decisions is corporate sustainability report. Sustainability is about long-termvalue creation not only for company but also for employees, customers, the industry sector, investors and thecommunities where the company does business. The ability of company to create long-term value is based on itsunderstanding and response to demands of society and on recognizing that environmental, social, economicaland ethical factors affect the business strategy. This article identifies drives for organization to adopt corporatesocial responsibility and produce corporate sustainability report.